Ex vivo lung perfusion: recent advancements and future directions - Nakata, Kentaro; Alderete, Isaac S.; Hughes, Benjamin A.; Hartwig, Matthew G. (Frontiers in Immunology, 2025)
Ex-vivo lung perfusion (EVLP) has emerged as a transformative technique in lung transplantation, offering a solution for evaluating and rehabilitating donor lungs that would otherwise be deemed unsuitable. This review article examines the significant advancements in EVLP technology and its application in clinical practice. We discuss the criteria for selection and rehabilitation of donor lungs, emphasizing the use of EVLP for lungs with compromised function due to factors like prolonged ischemic time and donor smoking history. Further, we elaborate on the technological advancements that have improved the functional assessment of lungs, including the development of more sophisticated perfusion solutions and the integration of artificial intelligence for real-time assessment. Additionally, we discuss the future prospects of EVLP, focusing on potential innovations in perfusion solutions, the integration of regenerative medicine and gene therapy to improve allograft quality. Through this comprehensive review, we aim to provide a clear understanding of the current status of EVLP and its promising future directions, ultimately contributing to improved outcomes in lung transplantation.